2019
DOI: 10.1002/clen.201800382
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating the Cadmium Toxicity and Growth‐Promotion in Paddy Rice by Photosynthetic Bacteria

Abstract: Cadmium (Cd) accumulation in rice and its subsequent transfer to food chain has become a major environmental issue worldwide. Low growth in plants and high toxicity toward the living organism are major drawbacks associated with Cd contamination. Effective immobilization and reducing Cd uptake by rice grains can be promising strategies to minimize its toxicity. Here, the authors report an effective method for Cd immobilization by inoculating photosynthetic bacteria known as Rhodopseudomonas palustris (RP) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…(2) Because most studies are limited to hydroponic or potted experiments in the laboratory, and very few experiments are applied to the field, some microorganisms cannot have beneficial effects under natural conditions, and the influencing factors may be caused by various factors. 77 On the one hand, the outdoor environment is uncontrollable. On the other hand, there are differences in soil properties, such as differental elements and original microorganisms in the soil and so on.…”
Section: Application and Prospects Of Microoganisms In Response To He...mentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Because most studies are limited to hydroponic or potted experiments in the laboratory, and very few experiments are applied to the field, some microorganisms cannot have beneficial effects under natural conditions, and the influencing factors may be caused by various factors. 77 On the one hand, the outdoor environment is uncontrollable. On the other hand, there are differences in soil properties, such as differental elements and original microorganisms in the soil and so on.…”
Section: Application and Prospects Of Microoganisms In Response To He...mentioning
confidence: 99%
“…Furthermore, the paddy field is generally polluted by different heavy metals; thus the application of microorganisms in paddy field needs to be further explored. At the same time, combined inoculation of different strains may have a more effective growth promotion effect in response to heavy-metal stress, which is a good choice for future crop planting research. Because most studies are limited to hydroponic or potted experiments in the laboratory, and very few experiments are applied to the field, some microorganisms cannot have beneficial effects under natural conditions, and the influencing factors may be caused by various factors . On the one hand, the outdoor environment is uncontrollable.…”
Section: Application and Prospects Of Microoganisms In Response To He...mentioning
confidence: 99%
“…During the past 10 years, increasing studies have shown the potential of using CdtB as biofertilizer for Cd remediation in rice (Jin et al 2021). Other studies have proposed the use of photosynthetic bacteria, such as Rhodopseudomonas palustris for Cd removal in paddy soil rhizosphere (Xiao et al 2019). In that study, R. palustris immobilization of Cd not only inhibited its uptake by plants but also increased fresh weight of rice seedlings with 40 mg kg À1 of Cd in soil, as well as reducing the Cd uptake and subsequent accumulation in rice grains (from 0Á65 to 0Á19 mg Cd per kg of grains).…”
Section: Rice Cropsmentioning
confidence: 99%
“…Due to the special gene of rice, its roots have a stronger ability to absorb cadmium than other crops such as corn and soybean. Therefore, it is crucial to monitor the content of cadmium in rice [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%